Exploring the narrative: Jerusalem and Jordan in the Bronze and Iron Ages - Steen, E. J. van der; Boertien, Jeannette; Mulder-Hymans, Noor (Library of Hebrew bible/Old Testament studies, 2014)
This volume brings together a number of scholars who use archaeology as a tool to question the sometimes easy assumptions made by historians and biblical scholars about the past. combining essays from both archaeologists and biblical scholars whose subject matter, whilst differing widely in both geographical and chronological terms, also shares a critical stance used to examine the relationship between 'dirt' archaeology and the biblical world as presented to us through written sources